High integrity joining and Repair of Gamma Titanium Aluminides - Paul Fitzgerald (2022)
Gamma Titanium Aluminide alloys are brittle, expensive, and difficult to repair using conventional fabrication techniques, so a unique and bespoke viable bonding technique utilising induction heating and argon gas shielding was investigated. Ti-45Al-2Mn-2Nb-0.8B Titanium Aluminide alloy was used which had been HIPped and electro-discharge machined into test pieces for bonding where the feedstock for the powder was generated via gas atomisation. The powder had a fine cellular microstructure and was used in a thin interlayer between the two surfaces to be bonded consisting of feedstock powder with cellulose and glycerol to form a paste. Analysis of small-scale porosity in the completed bonds showed the final bonds had minimal porosity. The hardness data indicated the interlayer was over-matched compared to the parent material. A limited number of LCF specimens showed that the high hardness of the interlayer causes the specimens to fail away from the interlayer as long as specimen preparation was performed correctly. Inadequate specimen preparation leads to potentially serious porous defects. The bonds produced were of good quality, at least as good as the parent material.